Increasing Product Attractiveness through Packaging Design and Ethical Labels in Brown Bread MSMEs - Raudatul Khamamah Hi. Laguna; Dian Safira J. Juanda; Cecilia Iriana Diva; Ramli Syarif; Sakinah Sudin (Takaza Innovatix Labs Ltd., 2026)
Chocolate bread MSMEs as part of the food sector have great potential in supporting the community's economy, but there are still many who face obstacles in terms of packaging and product labeling. MSMEs in this activity still market their products without unit packaging and without labels, so that the products lack identity and attractiveness in the eyes of consumers. This Community Service activity aims to increase the attractiveness and selling value of chocolate bread products through the design and implementation of packaging design and ethical labels that are simple, informative, and in accordance with the principles of business ethics. The methods used include observation of initial conditions, design of packaging sticker designs, sticker printing, and application of stickers on bread wrapping plastic. The results of the activity show that bread products that were previously sold without packaging and labels now have a more attractive and professional visual identity. The application of ethical packaging and labels has a positive impact on increasing interest in buying and selling products. Thus, packaging and labels not only function as protectors, but also as information and promotional media that are able to increase the competitiveness of chocolate bread MSMEs